The Etymology of Nyonya and Nona and their Language Contacts: Unilateral and Reciprocal Influence - Silvio, Moreira de Sousa; Tan, Raan Hann (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Among the ethnonyms recorded for the Chinese Peranakans of Indonesia, Malaysia, and Singapore, nyonya (or nonya) stands out, because it is perceived as a loanword and its origin is strongly disputed. The Pusat Rujukan Persuratan Melayu (the main reference of the Malay language in Malaysia, containing the dictionaries Kamus Dewan and Kamus Pelajar) and the Kamus Besar Bahasa Indonesia (the main reference in Indonesia; KBBI) register nyonya. However, scholars and dilettantes in the study of the Chinese Peranakan point out to different etymologies. One of these involves the word nona, which is found in Malay, in the Melaka Creole Portuguese, and in one dictionary of Baba Malay.